2010
DOI: 10.1007/s10586-009-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of broadcast and global combine operations in all-port wormhole-routed OTIS-Mesh interconnection networks

Abstract: OTIS (Optical Transpose Interconnection System) optoelectronic architecture is an attractive high-speed interconnection network. As a continuation for the research work performed on OTIS, this paper investigates broadcast and global combine communication operations on the promising all-port wormhole-routed OTIS-Mesh using the Extended Dominating Node (EDN) approach, referred to as EDN-OTIS-Mesh. The performance of broadcast and global combine operations is evaluated, both analytically and by simulation, in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…, n} with i = j, are intended to model the (longer) optical connections. The resulting OTIS network is denoted by OTIS-G. Of course, an OTIS network is dependent upon its base graph G, and numerous results have been proven for both specific base graphs and classes of base graphs (see, for example, the papers [1,3,7,8,17,18,19,23] and the references therein).…”
Section: Optical Transpose Interconnection Networkmentioning
confidence: 99%
“…, n} with i = j, are intended to model the (longer) optical connections. The resulting OTIS network is denoted by OTIS-G. Of course, an OTIS network is dependent upon its base graph G, and numerous results have been proven for both specific base graphs and classes of base graphs (see, for example, the papers [1,3,7,8,17,18,19,23] and the references therein).…”
Section: Optical Transpose Interconnection Networkmentioning
confidence: 99%
“…The experimental results showed that the OTIS-hypercube outperformed the hypercube network. Another research work evaluated the performance of broadcast and global combine communication operations on OTIS-mesh, in terms of number of communication steps, latency, and latency improvement [26]. Moreover, Hashemi-Najafabadi and Sarbazi-Azad [27] introduced and validated a mathematical performance model of adaptive wormhole routing in OTIS-hypercube.…”
Section: Related Workmentioning
confidence: 99%
“…So, one way to improve the runtime of the bucket sort algorithm is to run it on parallel or distributed architecture. Examples of these architectures are Optical Chained-Cubic Tree (OCCT) [15] and Optical Transpose Interconnection System (OTIS) and its variants, such as OTIS-Mesh, OTIS-Hypercube, and OTIS Hyper-Hexa Cell (OHHC) [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the sequential BS algorithm's steps, Fig. 1 shows an example of the BS algorithm's steps to sort 16 elements (i.e., n = 16) using 4 buckets (i.e., b = 4), where the 16 elements' values are generated uniformly over the interval [1,16]. According to Algorithm 1, in the first step, the size and the subintervals of the buckets are determined using Eqs.…”
mentioning
confidence: 99%
See 1 more Smart Citation